Extrachromosomal circular DNA (eccDNA): an emerging star in cancer - Ruomeng Li; Ying Wang; Jing Li; Xikun Zhou (BMC, 2022)
Abstract Extrachromosomal circular DNA (eccDNA) is defined as a type of circular DNA that exists widely in nature and is independent of chromosomes. EccDNA has attracted the attention of researchers due to its broad, random distribution, complex biogenesis and tumor-relevant functions. EccDNA can carry complete gene information, especially the oncogenic driver genes that are often carried in tumors, with increased copy number and high transcriptional activity. The high overexpression of oncogenes by eccDNA leads to malignant growth of tumors. Regardless, the exact generation and functional mechanisms of eccDNA in disease progression are not yet clear. There is, however, an emerging body of evidence characterizing that eccDNA can be generated from multiple pathways, including DNA damage repair pathways, breakage-fusion-bridge (BFB) mechanisms, chromothripsis and cell apoptosis, and participates in the regulation of tumor progression with multiplex functions. This up-to-date review summarizes and discusses the origins, biogenesis and functions of eccDNA, including its contribution to the formation of oncogene instability and mutations, the heterogeneity and cellular senescence of tumor cells, and the proinflammatory response of tumors. We highlight the possible cancer-related applications of eccDNA, such as its potential use in the diagnosis, targeted therapy and prognostic assessment of cancer.